2015
DOI: 10.1111/pce.12628
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‐specific protease 24 negatively regulates abscisic acid signalling in Arabidopsis thaliana

Abstract: Abscisic acid (ABA) is an important plant hormone integrating environmental stress and plant growth. Protein ubiquitination and deubiquitination are reversible processes catalysed by E3 ubiquitin ligase and deubiquitinating enzyme, respectively. Lots of E3 ubiquitin ligase and transcriptional factors modified by ubiquitination were reported to modulate ABA signalling. However, no deubiquitinating enzyme has been identified that functions in ABA signalling until now. Here, we isolated an ABA overly sensitive mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…Another interesting factor of our phosphoproteome analysis was the identification of the deubiquitinase UBP24 as MPK3-specific target. UBP24 is an upstream regulator of ABI2 for ABA and salt stress (69) and phosphorylation of UBP24 by MPK3 might influence protein turnover of certain MAPK stress pathway components.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting factor of our phosphoproteome analysis was the identification of the deubiquitinase UBP24 as MPK3-specific target. UBP24 is an upstream regulator of ABI2 for ABA and salt stress (69) and phosphorylation of UBP24 by MPK3 might influence protein turnover of certain MAPK stress pathway components.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas inhibition of PP2C activity is a reversible mechanism that regulates ABA signaling according to fluctuating ABA levels in response to environmental cues, degradation of PP2Cs is an irreversible decision that might lead to sustained ABA signaling when a stress situation persists. However, the degradation of PP2Cs or ABA receptors relies on their ubiquitination, which is a reversible process by the action of deubiquitinating enzymes that can further regulate the stability from core ABA signaling components (Zhao et al, 2016). In nature, both transient and sustained forms of stress occur; therefore, a double mechanism to abolish PP2C function seems to be better prepared to cope with different environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Much more work has been done with the characterization and function of plant ubiquitin E3 ligases compared with DUBs. Since their description by Yan et al (2000), around 10 Arabidopsis UBPs (ubiquitin proteases) have been characterized mainly based on the phenotypes of loss-of-function mutants: UBP1 and UBP2 are needed for resistance to canavanine, an amino acid analog (Yan et al, 2000); UBP14 is implicated in embryogenesis (Doelling et al, 2001); UBP3 and UBP4 play a role in pollen development (Doelling et al, 2007); UBP26 deubiquitinates histone H2B to regulate DNA methylation and heterochromatic silencing (Sridhar et al, 2007); and UBP24 has been recently shown to be a negative regulator of ABA signaling (Zhao et al, 2016). Other than for UBP26, none of the substrates of the USPs have been identified, thus precluding more in-depth mechanistic understanding.…”
Section: Introductionmentioning
confidence: 99%